Glucose and Insulin Modulate the Capacity of Endothelial Cells (HUVEC) to Express P-selectin and Bind a Monocytic Cell Line (U937) - Puente Navazo, Marta D.; Chettab, Kamal; Duhault, Jacques; Koenig-Berard, Elisabeth; McGregor, John L. (Thrombosis and Haemostasis, 2001)
Diabetes mellitus is associated with increased prevalence of endothelial cell dysfunction and vascular diseases. Mechanisms leading to alterations in endothelial cell function are poorly understood. We report here that hyperglycaemia results in the expression of endothelial adhesion molecules involved in leukocyte adhesion and extravasation. Incubation of human umbilical cord endothelial cells (HUVEC) with 25 mM glucose induced the expression of P-selectin. This effect was reversed by the addition of 1 nM insulin. Moreover, increased ICAM-1 expression was observed upon HUVEC incubation with 25 mM glucose. Increased adhesion of U937 cells (a monocytic cell line) to endothelial cells cultured with 25 mM glucose was observed. High glucose-induced monocytes cell adhesion was inhibited by an anti-P-selectin monoclonal antibody (LYP20). These results show that high glucose concentration activates endothelial cells leading to monocytes adhesion providing further evidence that hyperglycaemia might be implicated in vessel wall lesions contributing to diabetic vascular disease.Present address: Dr. M. D. Puente Navazo, Centre Pluridisciplinaire d’Oncologie, ISREC, Epalinges, Switzerland
Keywords: Endothelial cells; P-selectin; hyperglycaemia